Quantitative comparison between the commercial software STRATOS® by Philips and a homemade software for voxel-dosimetry in radiopeptide therapy. Issue 1 (February 2015) - Grassi, E.; Fioroni, F.; Ferri, V.; Mezzenga, E.; Sarti, M.A.; Paulus, T.; Lanconelli, N.; Filice, A.; Versari, A.; Iori, M.
Abstract Background Targeted radionuclide therapy is a rapidly growing modality. A few commercial treatment planning systems are entering the market. However, some in-house systems are currently developed for a more flexible and customized dosimetry calculation at voxel-level. For this purpose, we developed a novel software, VoxelMed, and performed a comparison with the software STRATOS. Methods The validation of both of them was undertaken using radioactive phantoms with different volume inserts. A cohort of 10 patients was also studied after a therapeutic administration of 177Lu-labelled radiopeptides. The activity, number of disintegrations, absorbed dose and dose-volume histogram (DVH) were calculated for the phantoms and the kidneys in patients, which were the main critical organs at risk in this study. Results In phantoms the absorbed doses computed with VoxelMed and STRATOS agree within 5%. In patients at the voxel-level the absorbed dose to kidneys (VoxelMed: mean 0.66 Gy/GBq) showed a limited difference of 5%, but with a remarkable range (−40%, +60%) between the two software packages. Voxel-dosimetry allows to estimate the dose non-homogeneities in volumes, which may be evaluated through DVHs. Conclusion This study demonstrates that a fully 3D voxel-dosimetry with multiple SPECT images is feasible by using home-made or commercial software package and absorbed dose results obtained are similar. The main difference between the studied tools was observed in the activity integration method (effective vs physical half-time to time activity curve tail). We believe that an effective half-time integration method produces a more accurate approximation of clinical uptake and resultant dosimetry.